Integrated Pathways of COX-2 and mTOR: Roles in Cell Sensing and Alzheimer’s Disease - Tyagi, Arti; Kamal, Mohammad A.; Poddar, Nitesh Kumar (Frontiers in Neuroscience, 2020)
Cyclooxygenases (COX) are enzymes catalyzing arachidonic acid into prostanoids. COX exists in three isoforms: COX-1, 2, and 3. COX-1 and COX-2 have been widely studied in order to explore and understand their involvement in Alzheimer’s disease (AD), progressive neuro-inflammatory dementia. COX-2 was traditionally viewed to be expressed only under pathological conditions and to have detrimental effects in AD pathophysiology and neurodegeneration. An increasing number of reports are, however, coming up which point to much more complex roles of COX-2 in AD. Mammalian/mechanistic target of rapamycin (mTOR) has been considered as a hub that integrates multiple signaling cascades, some of which are also involved in AD progression. COX-2 and mTOR are both involved in environmental sensing, growth, and metabolic processes of the cell. They are also known to act in co-operation in many different cancers and thus, their role together in normal cellular functions as well as AD has been explored in this review. Some of the therapeutic approaches targeting COX-2 and mTOR in AD and cancer are also discussed.